2017
DOI: 10.1007/s10096-017-2957-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B vaccination status in an at-risk adult population: long-term immunity but insufficient coverage

Abstract: In France, hepatitis B (HB) vaccine has been offered to all infants since 1994, and was proposed to all children aged 11 years from 1994 to 1998. Nevertheless, HB vaccine hesitancy may result in low vaccination coverage in present-day at-risk adults. We aimed to determine HB vaccination coverage in adults attending a free testing center for sexually transmitted infections (STI). As part of routine care, three classes of data were anonymously collected from attendees over a 3-month period: results of HB serolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…For young adults, immunocompromised or not, HBV vaccination coverage is insufficient with a rate of only 55.3% [22,23]. This vaccine is nonetheless recommended in cancer patients as in the general population, with the same objective of 95% vaccination rate.…”
Section: Discussionmentioning
confidence: 99%
“…For young adults, immunocompromised or not, HBV vaccination coverage is insufficient with a rate of only 55.3% [22,23]. This vaccine is nonetheless recommended in cancer patients as in the general population, with the same objective of 95% vaccination rate.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the knowledge and the acceptability of recommended vaccinations in patients with chronic conditions, focusing mainly on single vaccines [17][18][19][20][21][22], but no such studies have been reported in Italy to the best of our knowledge, and the reasons for the low coverage have not been well investigated [10,11,21]. Therefore, the aims of this survey were to evaluate the knowledge of and attitudes and adherence to recommended vaccinations among patients with chronic diseases in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Several vaccination programs have been implemented all over the world for the individuals who due to epidemiological, health, occupational, or behavioral conditions are at higher risk of contracting infectious diseases [1]. Among these groups, it is well known that adults, especially those older or with chronic health conditions, are at higher risk of severe illness or complications from infection with rates of vaccination coverage also considerably lower than those established by the objectives of the immunization programs [2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%